Echinopsis chilensis (Friedrich et rowland): an endemic breeding site for Drosophilla pavani Brncic 1957 - Manriquez, G.=700 1 Benado, M.
(Es, En)
Ilus., 8 ref.
Keywords: INSECTA; ORGANISMOS INDIGENOS; DROSOPHILA; CHILE; ECHINOPSIS CHILENSIS; DROSOPHILA PAVANI; REVISTA CHILENA DE ENTOMOLOGIA